IMPLEMENTASI PENGGUNAAN SOFTWARE ACCURATE DALAM PENYUSUNAN LAPORAN KEUANGAN SEBAGAI DASAR PENGUKURAN KINERJA KEUANGAN (Studi Kasus Pada UMKM Royyan Collection) - Setyowati, Listiana Nur; Widiastuti, Retno; Oktavia, Fathimatuz Zahro Fazda (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to describe the application of Accurate in preparing financial statements, writing technical instructions for applying Accurate and seeing financial performance based on financial reports that have been prepared. The object of this research is MSMEs engaged in the textile industry. The data collection methods used are interviews and documentation. The results showed that the entity had difficulties preparing financial reports and calculating business profits using manual recording. The application of Accurate Software can prepare financial reports automatically and accurately so that financial management can be carried out more precisely and efficiently. The technical guidelines prepared have been tailored to the needs of the entity to support the use and facilitate the application of Accurate Software. The financial performance measured based on the financial statements that have been made shows that the entity's ability to generate net income, profit with assets and profit with equity is still in the unfavorable category because of the lack of financial performance. The performance falls into the poor category because the percentage is below the standard financial ratio.